Perbandingan Kecerdasan Spiritual, Karakter Religius, dan Perilaku Prososial Siswa Madrasah Tsanawiyah (MTs) dengan Siswa Sekolah Menengah Pertama (SMP) - Sartono, Dwi Adi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study was encouraged by some indicators showing the problems regarding spiritual intelligence, religiosity, and sociability of students in Islamic and Public Junior High schools. This research aimed to determine the differences in spiritual intelligence, religiosity, and sociability of students in the Islamic Junior High School from the students in Public Junior High School in Logas Tanah Darat. This study is comparative research with a quantitative approach. The data were collected using questionnaires. The population number was 459 and the 176 samples were drawn using a quota sampling technique. The data were then analyzed using the “t” test formula for a large unrelated sample. The hypothesis test showed that, firstly, there was a difference in spiritual intelligence of the students in Islamic Junior High School from the students in Public Junior High School in Logas Tanah Darat (sig. 0.003<0.05). Second, there was no difference in the religiosity of the students in Islamic Junior High School from the students in Public Junior High School in Logas Tanah Darat District (sig. 0.337>0.05). Third, there was no difference in the sociability of the students in Islamic Junior High School from the students in Public Junior High School in Logas Tanah Darat (sig. 0.053>0.05) ).